Produção e qualidade de raiz tuberosa de cultivares de batata-doce no oeste do Paraná - Gomes, Simone Damasceno; Moro, Edemar [UNESP]; Cereda, Marney Pascoli; Roesler, Patrícia Vieira Sutil de Oliveira; Kummer, Ana Carolina Barbosa (Editora da Universidade Estadual de Maringá - EDUEM, 2008)
The objective of this work was to evaluate sweet potato cultivars with starch processing capability, on two cultivation periods, in the western region of Paraná (Brazil). Sweet potato was grown at Marechal Cândido Rondon, Paraná State (24º33'40S and 54º04'12W), at a mean annual temperature between 14 and 28ºC. The experiment was designed in complete randomized blocks, in a factorial scheme of 4 cultivars (CNPH 003, CNPH 004, Brazlândia Roxa, and Brazlândia Rosada) and 2 cultivation periods (115 and 183 days), with four repetitions. The evaluated parameters were the root productivities (t ha-1) and the physical and chemical root composition (humidity, pH, acidity, starch, total soluble sugars and fibers). Data was submitted to an analysis of variance (Anova) and the means were compared by the Tukey test at 5% of probability. Results indicated that sweet potato yield at the cultivars was higher during the 183 day cultivation period (average of 9.14 t ha-1) than during the 115 day cultivation period (average of 4.25 t ha-1). Thus the CNPH 003 cultivar seems to be a better indication for starch extraction, due to the lowest fiber content in the root, the driest mass content and the largest yield of starch per area.

Objetivou-se avaliar cultivares de batata-doce com aptidão ao processamento de fécula, em duas épocas de colheita. O cultivo da batata-doce foi realizado em Marechal Cândido Rondon, Estado do Paraná (latitude 24º33'40S e longitude 54º04'12W), com temperatura média anual entre 14 e 28ºC. O delineamento experimental foi de blocos ao acaso, em esquema fatorial 4 x 2, com 4 repetições, examinando-se os fatores cultivar (CNPH 003, CNPH 004, Brazlândia Roxa e Brazlândia Rosada) e épocas de colheita (115 e 183 dias). As características avaliadas foram rendimento de raiz tuberosa (t ha-1) e composição física e química da raiz tuberosa (umidade, pH, acidez, fécula, açúcares solúveis totais e fibras). Foi realizada análise de variância e as médias dos tratamentos comparadas pelo teste de Tukey ao nível de 5% de probabilidade. Os cultivares produziram mais na segunda época do que na primeira época de colheita, com média de 9,14 e 4,25 t ha-1, respectivamente. Para a produção de fécula a cultivar CNPH 003 se mostrou mais indicado, dentre os demais, em função da apresentação de raízes com menor teor de fibras, maior teor de massa seca e maior média de fécula por área.
Yield and quality of roots of sweet potato cultivars in the western region of Paraná
Keywords: Fibers; Ipomoea batatas; Soluble sugars; Starch content; Ipomoea batatas; fécula; açúcares solúveis; fibras